2019
DOI: 10.1002/app.48574
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized polyesters derived from glycerol: Selective polycondensation methods toward glycerol‐based polyesters by different catalysts

Abstract: Convergence of biodegradability and functionality is a major direction of new generation bio-based materials. Functionalized aliphatic polyesters based on glycerol are synthesized by solvent-free polycondensation directly. The aim is to prepare linear polyesters with pendant hydroxyl groups along the polymer backbone. The performance of the sustainable biocatalyst Novozyme-435 (an immobilized form of Candida antarctica lipase B) and the metal-based catalyst scandium trifluoromethanesulfonate (also known as sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…For the synthesis of glycerol-based polyester, the CALB amount of 10 wt % is generally employed in both solvent-free and in solution reactions. 22 , 23 , 27 , 29 However, Gameiro et al 41 reported the use of a CALB amount of 25 wt % for the enzymatic synthesis of poly(glycerol succinate) in a supercritical carbon dioxide solution and the formation of polymers with M n up to 3.5 kDa. Uyama et al 25 reported the use of a CALB amount of 15 wt % for the synthesis of PGS with M w = 19.0 kDa and y 1,2,3D = 16% from vinyl sebacate in bulk at 60 °C for 8 h. These PGS molecular weight and the fraction of the dendritic unit are similar to those achieved by us when using a CALB amount of 13.6 wt % ( M w = 16 kDa and y 1,2,3D = 20%).…”
Section: Resultsmentioning
confidence: 99%
“…For the synthesis of glycerol-based polyester, the CALB amount of 10 wt % is generally employed in both solvent-free and in solution reactions. 22 , 23 , 27 , 29 However, Gameiro et al 41 reported the use of a CALB amount of 25 wt % for the enzymatic synthesis of poly(glycerol succinate) in a supercritical carbon dioxide solution and the formation of polymers with M n up to 3.5 kDa. Uyama et al 25 reported the use of a CALB amount of 15 wt % for the synthesis of PGS with M w = 19.0 kDa and y 1,2,3D = 16% from vinyl sebacate in bulk at 60 °C for 8 h. These PGS molecular weight and the fraction of the dendritic unit are similar to those achieved by us when using a CALB amount of 13.6 wt % ( M w = 16 kDa and y 1,2,3D = 20%).…”
Section: Resultsmentioning
confidence: 99%
“…Without further purification, the resulting polymer has an Mn and Đ of 19.2 kDa and 1.2, with only 6% of 1,2-linked glycerol polyesters. The third is the enzyme-catalyzed polycondensation reaction between glycerol and diacid/diester [ 19 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Finally, glycerol polyol polyesters were synthesized without the addition of a catalyst [ 58 ].…”
Section: Polyol Polyesters From Glycerol and Sugar Alcohols (Alditmentioning
confidence: 99%
“…Successful synthesis of linear polyol-polyesters can lead to development of new sustainable surfactants [1][2][3][4][5] and there is particular focus on the use of carbohydrates as a renewable resource for polymer design, 3,6,7 because they bring a rich variety of structures with abundant stereochemical diversity. 8 Carbohydrates such as glucose, glycerol and D-sorbitol contain multiple hydroxyl groups and are emerging as alternative hydrophilic moieties in surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 To overcome concerns regarding control of molecular weight and side-product formation, the linkage of polyols using dicarboxylic acids has been reported in surfactant design, an example being the synthesis of polyglycerol diacid esters. 1,5,16 These are then esterified with fatty acids to introduce a hydrophobic moiety, and have been commercialised under the brand NatraGem™. 17 Condensation polymerisations conducted using dicarboxylic acids and polyols, such as glycerol and D-sorbitol, have been widely performed in the bulk, and thus are solvent-free systems.…”
Section: Introductionmentioning
confidence: 99%